Study of clinical profile and associated anamalies and surgical outcome of spina bifida - Venkatesh, K. L. (International Surgery Journal, 2016)
Background:Neural tube defects (NTDs) are a group of congenital anomalies characterized by defects in dorsal midline structures, including neural tissue, dura, muscle, bone and/or skin. The clinical presentations and the follow-up of these patients require attention to various end organs besides the nervous system. The aim was to evaluate the clinical profile and surgical outcome of children with spina bifida. Methods: Out of a total of 74 patients treated at our institute for spina bifida between June 2013 to August 2015, 74 cases of spina bifida were analyzed retrospectively and prospectively. The clinical profile, radiological findings and urodynamic studies were recorded. Craniospinal MRI was done in patients to screen for Arnold Chiari malformations and monitoring of hydrocephalus was done as a management protocol at our institute for these children. All these patients except two underwent surgery for correction and closure of the spinal defect. Associated anomalies were treated accordingly. They were clinically assessed over a mean follow up period of 11months ranging from 2months to 2 ½ years. Results:73% of the patients presented in the neonatal age group. Of which, 72% presented with a visible sac over the back.72% of the cases were myelomeningocoeles. 79% of the defects were in the lumbosacral region. 30% presented with sensorimotor loss or bladder bowel incontinence. Sensorimotor improvement was seen in 12.5% after repairing the defect with the help of physiotherapy and braces. 30% of the patients were diagnosed to have hydrocephalus, of which 33% required a CSF diversion procedure. The postoperative course of spina bifida repair was found to be uneventful in 90% of the patients. Conclusions:A multidisciplinary approach is required to address this disease. Early diagnosis, surgical management and rehabilitation can prevent further neurological damage and can improve quality of life in patients with spina bifida.